Neutrophil extracellular traps induced by activated platelets contribute to procoagulant activity in patients with colorectal cancer. Issue 180 (August 2019) - Zhang, Yan; Wang, Chunxu; Yu, Muxin; Zhao, Xinyi; Du, Jingwen; Li, Yueyue; Jing, Haijiao; Dong, Zengxiang; Kou, Junjie; Bi, Yayan; Novakovic, Valerie A.; Zhou, Jin; et al.
Abstract: Patients with colorectal cancer (CRC) are at increased risk of venous thrombosis, but the precise mechanisms of thrombogenesis in CRC remain largely unknown. We aimed to identify the novel role of neutrophil extracellular traps (NETs) in the induction of procoagulant activity (PCA) in CRC, and to evaluate its interactions with platelets and endothelial cells (ECs). In this study, we first showed that the levels of NETs in the peripheral blood of CRC patients were increased in parallel with cancer progression and reached significance in stage II patients compared to healthy subjects. In addition, neutrophils from CRC patients were more prone to produce NETs, resulting in shortened coagulation time, significantly increased thrombin-antithrombin (TAT) complexes and fibrin fibrils compared to healthy controls. Furthermore, platelets from CRC patients stimulated healthy neutrophils to extrude NETs, which could be inhibited by the depletion of HMGB1. Conversely, NETs from CRC patients could also induce the exposure of PS on platelets, leading to markedly enhanced PCA. Importantly, ECs were also converted to a procoagulant phenotype when exposed to NETs from CRC patients. The PCA of NETs-activated platelets or ECs could be inhibited either by the cleavage of NETs with DNase1 or the blockage of histone with activated protein C (APC). Our results reveal the complex interactions between neutrophils, platelets and ECs and their potential role in the hypercoagulable state in CRC. We propose that NETs may provide new therapeutic targets to combat the thrombotic consequences of CRC. Highlights: Neutrophils from CRC patients were more prone to produce NETs and promote PCA. Platelets and NETs formed a vicious cycle in the hypercoagulable state in CRC. CRC-derived NETs converted ECs to a procoagulant phenotype. NETs may become a potential marker and target in the prevention of VTE in CRC.